2018
DOI: 10.1111/1754-9485.12790
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CT imaging in a novel form of high‐dose‐rate intraoperative breast radiation therapy

Abstract: Computed tomography findings prompted treatment alterations in the majority of patients treated with PB-IORT to enhance tissue conformity and to sculpt the radiation dose away from normal tissues. CT imaging is unique to PB-IORT. These findings suggest the potential clinical superiority of PB-IORT given its allowance for patient-specific alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Initial studies have demonstrated the feasibility of this approach with promising short-term outcomes in 2 studies, and larger studies are currently underway. [99][100][101] IORT A total of 150 articles were identified; the final review included 2 randomized trials, 26 prospective/registry studies, and 3 treatment guidelines. Key studies are presented in Table 4.…”
Section: Ultrashort Partial Breast Irradiationmentioning
confidence: 99%
“…Initial studies have demonstrated the feasibility of this approach with promising short-term outcomes in 2 studies, and larger studies are currently underway. [99][100][101] IORT A total of 150 articles were identified; the final review included 2 randomized trials, 26 prospective/registry studies, and 3 treatment guidelines. Key studies are presented in Table 4.…”
Section: Ultrashort Partial Breast Irradiationmentioning
confidence: 99%
“…The use of intraoperative volumetric real-time imaging to evaluate applicator placement and optimize the treatment plan is only feasible if an imaging device that can calculate density relative to water, such as computed tomography (CT), O-arm cone beam CT (CBCT), and C-arms CBCT [5,6], is available in the operating room (OR) [7,8]. Other systems are under development to enhance the accuracy of the dose administered in IORT treatments [9].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] To some extent, conventional breast IORT is an operator-dependent technique limited by the lack of image guidance. Thus, it is logical to apply intraoperative computed tomography (CT) imaging in patients undergoing PBI using high-dose-rate brachytherapy for confirmation of applicator placement and treatment planning as reported by Hassinger et al 12 in this issue of the Journal of Medical Imaging and Radiation Oncology based on earlier work of the investigators. 13 The investigators showed that intraoperative CT imaging in 103 patients resulted in applicator adjustment in 26% of patients and dosimetry modifications in 79% of patients.…”
mentioning
confidence: 99%
“…17 Image-guided radiation therapy using CT imaging as per the study of Hassinger et al may not be an option at many centres due to the requirement for a CT on rails system. 12 Other three-dimensional (3D) image guidance modalities such as 3D ultrasound which has been used in external beam PBI 18 may provide comparable improvements in applicator placement and dosimetry as CT imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation